Syntactical Scrutiny: Inaccuracies in the Lesson Planning of Non-Language Pre-service Teachers - Antonio, Arnie (International Journal of Arts, Sciences and Education, 2021)
This study scrutinized the syntactical inaccuracies in the lesson planning of the 21 non-language preservice teachers at Isabela State University San Mariano Campus. The data collected were thoroughly analyzed using Gass and Selinker's EA model. Sentence fragments, article issues, run-on sentences, prepositional issues, SV agreement, and verb tenses are all noticeable results at the syntactical level of linguistics. These imprecisions are caused by two factors: (1) the students' incapability to master the target language's rules and structure; and (2) the L1's interference with the target language's learning.